Grounding accumulation by dispossession in everyday life. Issue 1 (13th April 2015) - Luke Bennett, Professor Antonia Layard, Mr; Hodkinson, Stuart; Essen, Chris
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This paper aims to ground Harvey's (2003) top-down theory of "accumulation by dispossession" in the everyday lives of people and places with specific focus on the role of law. It does this by drawing upon the lived experiences of residents on a public housing estate in England (UK) undergoing regeneration and gentrification through the Private Finance Initiative (PFI). Design/methodology/approach – Members of the residents association on the Myatts Field North estate, London, were engaged as action research partners, working with the researchers to collect empirical data through surveys of their neighbours, organising community events and being formally interviewed themselves. Their experiential knowledge was supplemented with an extensive review of all associated policy, planning, legal and contractual documentation, some of which was disclosed in response to requests made under the Freedom of Information Act 2000. Findings – Three specific forms of place-based dispossession were identified: the loss of consumer rights, the forcible acquisition of homes and the erasure of place identity through the estate's rebranding. Layard's (2010) concept of the "law of place" was shown to be broadly applicable in capturing how legal frameworks assist in enacting accumulation by dispossession in people's lives. Equally important is the ideological power of law as a discursive practice that ultimately undermines resistance to apparent injustices. Originality/value – This paper develops Harvey's concept of accumulation by dispossession in conversation with legal geography scholarship. It shows – via the Myatts Field North estate case study – how PFI, as a mechanism of accumulation by dispossession in the abstract, enacts dispossession in the concrete, assisted by the place-making and ideological power of law.